Respiratory virus detection during the COVID‐19 pandemic in Queensland, Australia - Asmaa El‐Heneidy; Robert S. Ware; Jennifer M. Robson; Sarah G. Cherian; Stephen B. Lambert; Keith Grimwood (Elsevier, 2022)
Abstract Objective: To determine if non‐pharmaceutical interventions (NPIs) impacted on respiratory virus detections in Queensland, Australia, during the COVID‐19 pandemic year of 2020. Methods: We analysed weekly counts of influenza, human metapneumovirus, parainfluenza, respiratory syncytial virus, rhinovirus, and adenovirus available from a Queensland laboratory network for the year 2020. These were compared with averaged counts from 2015 to 2019. Results: Overall, 686,199 tests were performed. The timing of NPI implementation was associated with a sharp and sustained decline in influenza, where during the typical annual influenza season (weeks 23-40) no cases were detected from 163,296 tests compared with an average of 26.1% (11,844/45,396) of tests positive in 2015-2019. Similar results were observed for human metapneumovirus and parainfluenza. Respiratory syncytial virus detections also declined but increased in weeks 48-52 (5.6%; 562/10,078) to exceed the 2015-2019 average (2.9%; 150/5,018). Rhinovirus detections increased after schools reopened, peaking in weeks 23-27 (57.4%; 36,228/63,115), exceeding the 2017-2019 detections during that period (21.9%; 8,365/38,072). Conclusions: NPIs implemented to control COVID‐19 were associated with altered frequency and proportions of respiratory virus detections. Implications for public health: NPIs derived from influenza pandemic plans were associated with profound decreases in influenza detections during 2020.